Tantangan dan Inovasi Pendidikan Islam di Era Digital: Membangun Generasi Berkarakter di Era Modern - Okta Farhan Syahendra (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The challenges facing Islamic teaching require development to ensure its relevance and adequacy. The research conducted examines the challenges and advances in Islamic learning in the present day. The reason for this consideration is to distinguish advances in Islamic teaching and learning to form a bright generation of Muslims in modern times. The research method is a literature study (library literature) and analysis of various related materials in relevant books and journals. The discussion states that the utilization of ICT innovations, the development of portable applications, and the utilization of computer media are developments that can enhance the learning experience of students. However, challenges such as limited access to innovations and the increasing number of challenges to be overcome also raise concerns. The conclusion is that Islamic learning requires advancements related to innovative technologies, taking into account challenges such as limited access and the increasing breadth of challenges to be overcome. It is imperative that educators and governments work together to minimize these challenges and ensure that Islamic teaching remains relevant and valuable in the age of computerization.